Oil-based versus water-based contrast media for hysterosalpingography in infertile women of advanced age, with ovulation disorders or a high risk for tubal pathology: study protocol of a randomized controlled trial (H2Oil2 study) - K. Rosielle; D. Kamphuis; N. van Welie; I. Roest; A. Mozes; E. J. P. van Santbrink; T. van de Laar; A. B. Hooker; A. G. Huppelschoten; W. Li; M. Y. Bongers; J. Stoker; et al. (BMC, 2022)
Abstract Background In women with unexplained infertility, tubal flushing with oil-based contrast during hysterosalpingography (HSG) increases ongoing pregnancy and subsequent live birth rates when compared to tubal flushing with water-based contrast. It is currently unclear whether an HSG with oil-based contrast also results in more ongoing pregnancies and live births in women of advanced age, women with ovulation disorders, and women with potential tubal pathology when compared to an HSG with water-based contrast. Methods We plan an international, multicentre, open-label, randomized controlled trial (RCT) studying three groups of infertile women who have an indication for tubal patency testing according to their treating physician and additionally; (1) are 39 years of age or older, (2) have an ovulation disorder or (3) have a high risk for tubal pathology based on their medical history. Women with an allergy for iodinated contrast medium are excluded, as are women with diabetes, hyperprolactinemia or untreated hyper- or hypothyroidism, and women with a partner with severe male infertility. After informed consent, women will be randomly allocated to the intervention, tubal flushing with the use of oil-based contrast during HSG or the control group, tubal flushing with the use of water-based contrast during HSG in a 1:1 ratio by the web-based system Castor. The primary endpoint will be ongoing pregnancy leading to live birth with conception within six months after randomization. Secondary outcomes are other pregnancy outcomes, used fertility treatments, adverse events and cost-effectiveness. Based on the expected ongoing pregnancy rate of 17% in the control group and 27% in the intervention group, the sample size will be 930 women (465 per group). Study inclusion is expected to be complete in four years. Discussion This multicentre RCT will establish whether, for women of advanced age, women with ovulatory disease, and women who have a high risk for tubal pathology, there is a fertility enhancing effect of tubal flushing with oil-based contrast during HSG and whether the use of this contrast medium is cost-effective. Trial Registration The study was prospectively registered in the Netherlands Trial Register on August 1st 2019 as 'H2Oil2' (reference number NL7925, https://www.trialregister.nl/trial/7925 ).